Development of Mobile Learning NARACY (Financial Literacy) as a Learning Media for Social Studies Subjects in Junior High School - Alfania, Sheila; Wahyuningtyas, Neni; Prasat, Ravinesh Rohid (International Journal of Social Learning (IJSL), 2024)
The industrial revolution 4.0 is characterized by technological disruption that affects the education system. One of the implementations of technology orientation in the learning process facilitated by teachers is through learning resources. Therefore, this study aims to produce a mobile learning product, NARACY, as a learning media to support financial literacy material activities for grade IX junior high school students. This research uses the Research & Development (R&D) method with the ADDIE model. This research and development showed a total percentage of material validators of 91.6% and media validators of 95%. At the same time, the trial results on grade IX students obtained an average percentage score of 93%. Based on these results, the NARACY application is very feasible to use as a medium for learning social studies in grade IX junior high school. This research and development is expected to be an innovative learning support media that can be used by teachers and students and is expected to facilitate diverse student learning styles. Suggestions for further research include testing the product's effectiveness by conducting experimental activities in the classroom and providing various themed features on the product. They can be disseminated through the Google PlayStore platform.